Family savings diversification in the financial system in Peru - Santos Jiménez, Néstor (2011)
The monetary savings resulting from a family effort to preserve and increase in yields as achieving greater availability of funds in the future. For money to grow in value, performance, measured by the effective annual interest rate must be higher than inflation; in addition, the risk can be controlled by saving decisions according to the options offered by the peruvian financial institutions authorized. The information analyzed for the years 2009 and 2010, confirms that interest rates in the local market depending on the amount of money, the term of the deposit, and the status and prospects of the bank.